Deficiency in Lipoteichoic Acid Synthesis Causes a Failure in Executing the Colony Developmental Program in Bacillus subtilis - Mamou, Gideon; Fiyaksel, Osher; Sinai, Lior; Ben-Yehuda, Sigal (Frontiers in Microbiology, 2017)
Colonies are an abundant form of bacterial multicellularity; however, relatively little is known about the initial stages of their construction. We have previously described that colony development of the soil bacterium Bacillus subtilis is a highly ordered process, typically initiating with the formation of extending cell chains arranged in a Y shape structure. Furthermore, we demonstrated that Y arm extension is a key for defining the size of the future colony. Here we conducted a genetic screen surveying for mutants deficient in these early developmental stages, and revealed LtaS, the major lipoteichoic acid (LTA) synthase, to be crucial for execution of these events. We found that the ltaS mutant fails to produce proper Y shape structures, forming extremely elongated chains of cells with no evidence of chain breakage, necessary for Y shape formation. Furthermore, we show that frequent cell death at the tips of the cell chains is a major cause in limiting arm extension. Collectively, these perturbations lead to the production of a small sized colony by the mutant. Thus, deficiency in LTA synthesis causes a mechanical failure in executing the colony developmental program.